Relationship between brazil and cia exhibited in counterspy magazine - Navega-Costa, Roberto Rigaud (2022)
In researches in the Central Intelligence Agency (CIA) database, a very curious document was found, which contained the publication of a volume of CounterSpy magazine, volume 3, number 4, of April/May 1979, containing an article written by Peter Gribbin reporting on the relationship between certain events that occurred in Brazil that would have been influenced by US governments through the CIA. The objective of this scientific article was to analyze the document prepared by this author, articulating it with the magazine that published it and with the CIA's attitude of storing such text in its database. To handle this task, the document analysis approach was used, a decision that brought a set of possibilities to analyze a document starting from the identification of certain characteristics contained in the process used in its making. As a result of this research, an article was obtained that informs the reader about the influence of the CIA at a critical moment in Brazilian history, the passage from the João Goulart government to the military regime that succeeded it, at the same time as some considerations can be made about the facts narrated by the author of the original document, the author himself, the journal that published it and the information service that archived it. The conclusion that could be reached is that the document studied is very rich in analytical possibilities and that it was not addressed to Brazilian readers, but to American citizens, aiming to destabilize the CIA before voters and taxpayers, in that country, and the purpose of this approach may have interested rival intelligence services, such as the KGB for example, in an attempt to harm the CIA, during the so-called Cold War.